Approach to the Assessment and Management of Adult Patients With Atopic Dermatitis: A Consensus Document. Section V: Consensus Statements on the Assessment and Management of Adult Patients With Moderate-to-Severe Atopic Dermatitis. Issue 1 (November 2018) - Hong, Chih-ho; Gooderham, Melinda J.; Albrecht, Lorne; Bissonnette, Robert; Dhadwal, Gurbir; Gniadecki, Robert; Grewal, Parbeer; Kirchhof, Mark G.; Landells, Ian; Lansang, Perla; Lynde, Chuck W.; Papp, Kim A.; et al.
This document is a concise, current, and practical guide for dermatologists and other health care providers managing adult patients with moderate-to-severe atopic dermatitis (AD). The recommendations made here are based on a consensus of specialists with extensive experience managing patients with AD. Topics reviewed in this publication include AD pathophysiology, assessment, comorbidities, and treatment options.